Equipment and technology for gas fluorination of polymers to improve their wear resistance under micro-impact loads - Martyniuk, A.; Stechyshyn, M.; Fedoriv, V.; Yaroshenko, P.; Liukhovets, V. (Problems of Tribology, 2026)
The article addresses the problem of improving the cavitation–erosion wear resistance of polymer materials operating under micro-impact loads in corrosive environments. It is shown that material degradation under such conditions has a complex mechano-corrosive nature, while corrosion processes can significantly accelerate the degradation of surface layers. In this regard, the use of polymers with high chemical resistance and inertness to aggressive media is relevant. However, the application of such highly resistant polymers is often economically impractical, which necessitates the development of methods for surface modification of available structural polymers to improve their performance properties. he aim of this work is to develop and scientifically substantiate a laboratory installation and technological parameters of the direct gas fluorination process for polymer materials in order to form a modified surface layer without altering the surface microgeometry and to increase their wear resistance. Polypropylene grade 21060, widely used in mechanical engineering, agricultural machinery, and food equipment due to its sufficient strength, chemical resistance, and processability, was selected as the object of the study. A laboratory installation for direct gas fluorination of polymers was designed using a gas mixture of 1% F₂ and 99% Ar followed by treatment with nitric oxide to neutralize active radicals. Experimental studies showed the formation of a modified surface layer about 5 μm thick with increased chemical inertness. It was established that fluorination significantly reduces the intensity of cavitation–erosion wear of polypropylene in various environments, confirming the effectiveness of the method for improving the durability of polymer components.